The podcaster's dilemma : decolonizing podcasters in the era of surveillance capitalism - Baham, Nicholas Louis, III, 1965-; Higdon, Nolan, 1983- (John Wiley & Sons, 2021)
"Broadcasting from Oakland, California, "the center of the known universe," Alicia Garza's podcast Lady Don't Take No! begins with the pronouncement "This show is pro-Black, pro-Queer, proudly Feminist, and pro-Do-Whatcha-Like. Every week, you are going to get the best of what goes on in my head, what we're lovin' on, what we're hatin' on, what we might be and what we aint gon do." Garza, a co-founder of the Black Lives Matter movement along with Patrisse Cullers and Opal Tometi, brings unfiltered community-based perspectives on everything from pop culture to politics. With broadcasts that elevate the voices of local and national Black activists, thinkers, and artists (e.g. Erika Huggins, W. Kamau Bell, Davey D., Lateefah Simon, Angela Rye, Laverne Cox, etc.), Garza's broadcast, "recorded with whatever was lying around," embodies the spirit of media freedom. Opening against the alternative hip hop beats of the Bay Area-based duo Latyrx, every broadcast sounds like a paradigm shift. Emerging in a summer of protest following the murder of George Floyd in Minneapolis, Minnesota and in the midst of the 2020 Coronavirus pandemic ("'rona and rebellion"), Lady Don't Take No! is an audio brick thrown the plate-glass window of corporate misinformation as Garza and her guests take back the narrative. Speaking as a member of the loving communities that she advocates for, Garza urges her listeners, "We do it for the culture, so the podcast is free 99 because we know with the country in chaos, the least we could do is keep you from putting your money anywhere else than where it's needed." Garza's Lady Don't Take No! is emblematic of the hundreds of podcasts that we have undertaken to review and critique in this book. We are interested in understanding how contemporary voices in digital media are built upon the legacy of post-WWII revolutionary radio in places like Algeria, Cuba, and Angola. We are attentive in the seamless flow between the home studios where so many of these broadcasts are recorded and communities of the voiceless and under-represented who now have a public forum for voicing the unadulterated truth of their lived experiences. We are interested in the pro-Black, pro-Brown, pro-AAPI, pro-Indigenous, pro-Queer, pro-working class voices that critique, interrogate, deconstruct, and engage in a revolutionary struggle of ideas against the slant and spin of a corporate news media that manipulates fear, resentment, and division in order to manufacture consent. We are interested in the broad explosion of intersectional voices in dialogue about everything from political organizing to plant-based diets. We are interested in the myriad coalitions being formed behind the microphone. We are interested in alternative and anti-capitalist funding models of decolonizing podcasts that emphasize cooperation and collaboration over competition. We are interested in podcasting as a medium of decolonization"--